2018
DOI: 10.1155/2018/7690501
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Oxidative, and Lipolytic Changes during Vacuum-Packed Storage of Dry-Cured Loin: Effect of Chestnuts Intake by Celta Pigs

Abstract: The effect of the inclusion of chestnuts in the finishing diet of Celta pig breed on the characteristics of dry-cured loin, a traditional Spanish dry-cured meat product, after the manufacturing process and the vacuum-packed storage was studied. In general, no significant differences between the diets (chestnut, mixed, and concentrate diet) were obtained for physicochemical (moisture, intramuscular fat, and titratable acidity) and lipolytic parameters. Lower pH and higher values for oxidation parameters (peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(75 reference statements)
3
6
0
1
Order By: Relevance
“…The main FFA in both, initial and final processing points, were C16:0, C18:1n‐9 and C18:2n‐6, which indicated that these fatty acids were the main FFA released (Lorenzo, ). The same profile was previously reported in dry‐cured loins (Lorenzo & Carballo, ; Pateiro et al ., ; Gómez et al ., ). The final amount of each individual free fatty acid should be the result of the balance between its release from glycerides and phospholipids and its oxidative degradation (Lorenzo & Carballo, ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The main FFA in both, initial and final processing points, were C16:0, C18:1n‐9 and C18:2n‐6, which indicated that these fatty acids were the main FFA released (Lorenzo, ). The same profile was previously reported in dry‐cured loins (Lorenzo & Carballo, ; Pateiro et al ., ; Gómez et al ., ). The final amount of each individual free fatty acid should be the result of the balance between its release from glycerides and phospholipids and its oxidative degradation (Lorenzo & Carballo, ).…”
Section: Resultssupporting
confidence: 87%
“…This fact is due to the ‘day 0’ in the present research was considered after salting and seasoning stages, which favour moisture losses. The moisture content in the final product was 38.84 g per 100 g, similar to those described by other authors in dry‐cured loins (Lorenzo & Carballo, ; Pateiro et al ., ; Gómez et al ., ). The other composition parameters were expressed as g per 100 g of dry matter.…”
Section: Resultsmentioning
confidence: 97%
“…SFA: Saturated fatty acids; MUFA: Monounsaturated fatty acids; PUFA: Polyunsaturated fatty acids; Data were obtained from [75,76,77,78,79,80,81]. …”
Section: Figurementioning
confidence: 99%
“…For example, salting above 20 g/L could either inhibit muscle neutral lipases and neutral and acid esterases or activate acid lipases ( Toldra & Flores, 1998 ). Therefore, the lipolytic changes in this type of meat products are attributed to lysosomal acid lipase and hormone-sensitive lipase with optimum pH values of 5.5 and 7.0–7.5, respectively ( Vestergaard, Schivazappa, & Virgili, 2000 ) when the pH value of dry-cured meat products generally varies between 5.5 and 6.2 ( Lorenzo, 2014 , Gómez et al, 2018 , Bou et al, 2022 ).…”
Section: Factors Influencing Lipolysis In Meat and Meat Productsmentioning
confidence: 99%